Avaliação do desempenho do cacto da espécie opuntia ficus-indica como coagulante no tratamento de água - Ferreira, Thayse Guilherme (2015)
Considering the water quality of watersheds in Brazil, the water treatment is an essential process for providing water suitable for human consumption. Coagulation, an essential step of water treatment, uses metal salts as coagulant. In order to provide more sustainable alternatives to the water treatment process, studies investigate the coagulation potential for different plant species. This work aimed to evaluate the performance of cactus extract from the Opuntia ficus-indica species as a possible natural coagulant in water treatment through coagulation testing and evaluating the efficiency of removal of water turbidity. Two methods for obtaining the coagulant were tested and the most effective one was pulverizing the cacti by drying it at 80oC for 24h, followed by trituration and sieving. Coagulation tests carried out took into consideration the initial turbidity that varied from 50 NTU to 300 NTU, pH of water (4, 6, 7, 8 and 10) and dosage of coagulant used that varied from 20 to 100 mg/L. The best results were found for water with high initial turbidity and coagulant dosages of about 60 mg/L. For the initial turbidity in the range of 200 NTU, for example, the removal reached 70.4% and 72.3% for the coagulant dosages of 60 and 80 mg/L, respectively. In the following tests, however, the 30 mg/L dosage was adopted since efficiency did not differ significantly from that obtained with twice the coagulant dosage. In that case, by applying 30 mg/L of coagulant, the efficiency for the 200 NTU initial turbidity reached 68.9%. The optimum pH range for the coagulation process was determined to be between 8 and 10. The possibility of cactus performing as an auxiliary coagulant with PAC was also evaluated and proved to have potential when compared to similar studies as shown by the 95.0% efficiency of removal after the use of both coagulants in a proportion of 50.0% each. The results show that the cactus has potential to be used as a natural coagulant and the execution of studies that aim to perfect the extraction method of its active constituent are suggested as a means to increase its efficiency.